2018
DOI: 10.1155/2018/9429265
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Hematological Cytopenia in Kidney Transplantation and the Challenges It Poses for Kidney Transplant Physicians

Abstract: Drug-induced hematological cytopenia is common in kidney transplantation. Various cytopenia including leucopenia (neutropenia), thrombocytopenia, and anemia can occur in kidney transplant recipients. Persistent severe leucopenia or neutropenia can lead to opportunistic infections of various etiologies. On the contrary, reducing or stopping immunosuppressive medications in these events can provoke a rejection. Transplant clinicians are often faced with the delicate dilemma of balancing cytopenia and rejection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(89 citation statements)
references
References 280 publications
(318 reference statements)
3
80
0
Order By: Relevance
“…Although CNIs often show benefits in rodent models of AD‐like pathology when given acutely (over a few days, or weeks), chronic treatment with these drugs (e.g., over months or years) causes systemic immunosuppression in otherwise healthy subjects, characterized, in part, by a drop in lymphocyte counts and other white blood cell changes (Gallo et al, 2006; Khalil et al, 2018; Koprak et al, 1996). Chronic lymphopenia could offset possible neurologic benefits achieved by long‐term CN inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although CNIs often show benefits in rodent models of AD‐like pathology when given acutely (over a few days, or weeks), chronic treatment with these drugs (e.g., over months or years) causes systemic immunosuppression in otherwise healthy subjects, characterized, in part, by a drop in lymphocyte counts and other white blood cell changes (Gallo et al, 2006; Khalil et al, 2018; Koprak et al, 1996). Chronic lymphopenia could offset possible neurologic benefits achieved by long‐term CN inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…As a potential therapeutic strategy for managing neurodegenerative disorders, it is notable that Q134R had no apparent direct effects on CN activity in vitro or in vivo , suggesting that Q134R acts downstream of CN activation. These observations suggest that Q134R could be used to target key CN‐mediated deleterious processes without triggering many of the adverse effects commonly ascribed to commercial CN inhibitors (Farouk & Rein, 2020; Khalil et al, 2018) (see additional discussion below).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To maintain self-sufficiency and governance, we have an active research unit that had churned out several review articles on transplantation between 2017 and 2019. is was to enable the team to acquaint themselves with transplant literature and keep abreast with the latest transplant developments. Review articles have been published on aspirin usage in kidney transplants [27], hematological cytopenia in kidney transplants [28], use of fluoroquinolone in BK virus nephropathy [29], cigarette smoking in kidney transplants [30], and dual kidney transplantations [31]. Another recent local-driven study in 2017 showed that lack of donors (71%), lack of awareness of the program (21.2%), and unwillingness to take risks (26.5%) were the main barriers to the progress of the program [32].…”
Section: Phase 4: Implementation and Consolidation Of Transplant Program (2013 To Current)mentioning
confidence: 99%